High-resolution ultrasound and power-Doppler - advances in pre-invasive diagnosis of solid breast lesions: our one-year experience - Brnić, Zoran (Radiology and oncology (Ljubljana), 1998)
The purpose of the study was to evaluate high-resolution ultrasound (HRUS) andpower-Doppler (CDE) in the differentiation of malignant from benign solid breast lesions. Patients and methods: HRUS and CDE examinations of solid breast masses were carried out in 25 women. Gray-scale criteria of malignancy and benignity were considered. The vessels of the lesion were classified as penetrant, peripheral and non-detectable with CDE. Final diagnose was obtainedcytologically and/or with biopsy. Results: HRUS detected more frequently irregularity of contours, heterogeneity and posterior attenuation than "classic" ultrasound. Laeral shadows in carcinomas were seen in a considerable number of cases, but this did not have any impact on the accuracyof diagnosis. HRUS facilitated the visualization of small carcinomas intraductal calcifications and papillomas. CDE detected flow in 15/25 lesions,of which 8 were malignant. Penetrant vessels were observed in 6/8 carcinomas and only in 2/17 benign changes; 6/11 fibroadenomas were avascular,and 4/11 with peripheral vessels. In 3/6 other benign lesions, the flow was shown with CDE. Conclusion: HRUS and CDE can successfully help in differentiation malignant from benign solid breast mass, and are a good adjunct to mammography and physical examination in the pre-invasive phas eof diagnostic process.
Keywords: Breast neoplasms; Methods; Ultrasonography; Ultrasonography, doppler, color; Ultrasonography, mammary